American woman, Italian style : Italian Americana's best writings on women - Albright, Carol Bonomo; Palamidessi Moore, Christine (Book collections on Project MUSE., 2011)
With writings that span more than 35 years, this book is a rich collection of essays that fleshes out the realities of today's Italian American women and explores the myriad ways they continue to add to the American experience.